Phylogenetic tree from cytb sequences of common voles, Microtus arvalis - Searle, Jeremy; Martínková, Natália; Barnett, Ross; Cucchi, Thomas; Struchen, Rahel; Pascal, Marine; Pascal, Michel; Fischer, Martin; Higham, Thomas; Brace, Selina; Ho, Simon; Quere, Jean-Pierre; et al. (Dryad Digital Repository, 2013)
TreeBase entry containing DNA sequence alignment of mitochondrial cytb gene, phylogenetic tree from the Bayesian inference analysis, details of the analysis. This constitutes Figure 2 in the paper.